Investigation of Biomedical Students' Attitudes toward Pharmacogenomics and Personalized Medicine: A Cross-Sectional Study - Josipa Bukic; Doris Rusic; Dario Leskur; Ana Seselja Perisin; Tin Cohadzic; Marko Kumric; Josko Bozic; Darko Modun (MDPI AG, 2022)
Background: The utilization of pharmacogenomics in everyday practice has shown several notable benefits. Keeping in mind the rising trend of applicability of pharmacogenomics and personalized medicine, we sought to compare the attitudes of future healthcare workers in different branches of the healthcare system. Methods: The present study was conducted as a questionnaire-based cross-sectional study in October of 2020. Students eligible to participate were all the students of the University of Split School of Medicine enrolled in the academic year 2020/2021. Results: The number of students that participated in the study was 503. Students were most interested in clinical examples of pharmacogenomics (31.4%) and the benefits of pharmacogenomics in clinical practice (36.4%). Furthermore, 72.6% of all students agreed that they should be able, in their future practice, to identify patients that could benefit from genetic testing. Conclusion: At the present time, the lack of education and appropriate clinical guidelines appear to be the major barriers to the clinical application of pharmacogenomics, especially in Croatia. Hence, in order to support health care professionals' evidence-based therapeutic recommendations with patients' pharmacogenomic data, universities should offer more pharmacogenomics education in their curricula.